Presentation and pathophysiology of neuro-COVID - Josef Finsterer; Fulvio Alexandre Scorza; Alexandra Scorza (BioExcel Publishing Ltd, 2021)
Letter to the Editor commenting on Orsucci D, Caldarazzo Ienco E, Nocita G, Napolitano A, Vista M. Neurological features of COVID-19 and their treatment: a review. Drugs Context. 2020;9:2020-5-1. https://doi.org/10.7573/dic.2020-5-1